Development and creation of a hydrodynamic liquid heating unit - Nussupbekov,B.; Oshanov,Y.; Ovcharov,M.; Mussenova,E.; Ospanova,D.; Bolatbekova,M. (Eastern-European Journal of Enterprise Technologies, 2022)
The work is devoted to the study of the parameters of an installation for heating a coolant using liquid forcing through throttle openings. A scheme of a full-size experimental stand has been developed and the principles of operation are described in detail. For visual observation of the state of the liquid at different angular speeds of rotation of the rotor, a transparent drum model is made. The influence of the shape of the rotor skirt and the depth of its immersion in the liquid on the filling capacity of the rotor cavity at an angular velocity from 42 to 314 rad/s has been determined. The optimal parameters of the depth of immersion of the drum skirt with a diameter of 0.5 m in the liquid, at low rotor speeds of 16, 24, 32 rad/s, were obtained. The angle of inclination is calculated and it is experimentally proved that for a conical shape it is 5 degrees. It was found that at angular velocities of the rotor more than 100 rad/s, the shape and depth of immersion of the skirt in the liquid do not affect the filling of the rotor, since the feed is higher than its flow through the throttle openings. It is shown that the use of rotational forces to heat the liquid allows using an electric motor with less power, since it is spent only on unwinding the rotor with the liquid. The calculated dependence of the liquid pressure on the side walls of the rotor, the liquid heating temperature on the angular velocity of rotation of the rotor and on two values of the area of the throttle openings, at 31.4·10–6 m2 and 64.34·10–6 m2, is obtained. When the total area of the throttle openings is doubled, the temperature of the liquid heating at the same angular velocities increases from 35.6 °C to 82.5 °C. The above installation parameters allow you to get hot water when using small shell-and-tube heat exchangers
Keywords: installation; inertial forces; throttling; pressure; temperature; rotor; liquid heating; pump; drum